Corruption as an obstacle for starting a new business in Serbia - Ivanovic-Djukic Vinko Lepojevic, Maja; Stefanovic, Suzana; van Stel, André; Ateljevic, Jovo (Senate Hall, 2019)
This paper examines the perceptions and actual experiences of SME owners and entrepreneurs in Serbia regarding the impact of corruption on the establishment of new businesses. It is based on primary research conducted in 2015 on a sample of 250 entrepreneurs and owners of small and medium-sized enterprises in Serbia. An original questionnaire was used for data collection. Our research shows that corruption is clearly present in Serbia as almost 60% of business owners in our sample admits to have used some form of corruption when they started their own business. Areas important for starting a business in which corruption is most present are: obtaining subsidies, grants, and other favorable sources of financing for starting a business; issuing construction permits; and registering property. The presence of corruption in these and other areas that are important for starting a business affect the time needed to start a business, the costs of its registration and provision of initial capital.
Keywords: Entrepreneurs|small and medium-sized enterprises|corruption|Serbia